Factors affecting military expenditures in the Asia-pacific: Evidence from a panel-data, Quantile regression, and FMOLS - Kadir Aden (Universitas Teuku Umar, 2023)
The current study investigates factors affecting military expenditures within the Asian-Pacific context. By doing so, a period ranging from 2005 to 2021 was selected with ten diverse countries from the region. Several statistical analyses consisting of an OLS, fixed & Random effect was performed. Whereas a quantile regression was also included to capture the omitted effects of the panel data. Likewise, an FMLOS was used to better evaluate the long-run effect and the relationships among the factors. According the findings, financial development (FND), Trade (TR) and Technological innovation have positive effect on defense expenditures, the following effect was backed by the FMOLS estimates which demonstrated a similar finding making the results more robust. On the other hand, economic growth (GDP) and bureaucratic effectiveness (BR) displayed a negative sign in the rise of military expenditures. At the same time, FDI inflow manifested a positive significant effect, but, only in the OLS model and through the upper percentiles. Overall, the research is the first to encompass several macroeconomic factors with other external variables to assess Asia-pacific security expenditures. And indeed, with the current global conflicts, it is hoped this research will provide a decent information about the ineffectiveness and effectiveness threshold of increasing defense expenditures.